KAJIAN KOMPONEN STRUKTUR PEMBENTUK FASAD BANGUNAN STASIUN BEOS - Choirul Ridwan; Astria Melanira (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2022)
Transportation is a basic human need in living life on earth as a social being, so that its development will be influenced by developments in science and technology. And mileage and transport capacity are problems that have always been a concern of humans in the development of transportation technology, including land transportation technology. The history of urban transportation modes in the colonial era only by land and sea, in this case the researcher wants to try to examine more deeply the architectural style of the BEOS Station building, which is one of the buildings of the Old Station in Jakarta which is still in operation today. Keywords : Transportation,Colonial, Architecture